2018
DOI: 10.1111/joss.12443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the color and size of the plate on the subjective ratings of, taste expectations concerning, and willingness‐to‐pay for, Asian noodles

Abstract: Two experiments were designed to investigate the effect of plate color and plate size on taste expectations, subjective ratings of, and willingness‐to‐pay for, Asian noodles and Italian pastas. Chinese participants viewed photographs of these foods served on plates of different colors and sizes, rated their liking, familiarity, taste expectations for the foods, and indicated how much they would be willing to pay for them. The foods were presented against the backdrop of store‐bought or computer‐edited colored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(42 reference statements)
1
6
1
Order By: Relevance
“…First, the results of this study revealed that plate size exerted an influence on Chinese participants' willingness to pay for the Asian noodles shown on the plate, and both plate size and plate color influenced their pleasantness, familiarity, and food‐plate congruency ratings of the foods. These results are in line with the findings of Zhao et al's (2018) Experiment 2 in which the same photos of noodles were used but the participants were not exposed to any priming. Collectively, the findings of these two studies suggest that the effects of receptacles on the Chinese participants' perception of Asian noodles are quite robust in well‐controlled lab‐based situations.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…First, the results of this study revealed that plate size exerted an influence on Chinese participants' willingness to pay for the Asian noodles shown on the plate, and both plate size and plate color influenced their pleasantness, familiarity, and food‐plate congruency ratings of the foods. These results are in line with the findings of Zhao et al's (2018) Experiment 2 in which the same photos of noodles were used but the participants were not exposed to any priming. Collectively, the findings of these two studies suggest that the effects of receptacles on the Chinese participants' perception of Asian noodles are quite robust in well‐controlled lab‐based situations.…”
Section: Discussionsupporting
confidence: 91%
“…Each participant came to a psychology laboratory on campus to take part in this study online at http://www.qualtrics.com, and the whole study lasted approximately 10 min. In order to control for the visual appearances of Asian noodles across different plates, we used the same photos (each subtending 240 pixels horizontally × 180 pixels vertically) of computer‐edited plates that Zhao et al (2018) used in their Experiment 2. As shown in Figure 1, approximately 50 g Asian noodles were served on a large‐ or small‐sized (diameter in 26 or 20 cm) plate in color red (H: 356%, S: 99%, B: 81%), blue (H: 218%, S: 42%, B: 55%), or white (H: 55%, S: 19%, B: 95%).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations